Upaya Promotif dan Preventif Melalui Pendidikan Kesehatan Tentang Kehamilan Risiko di Dusun Nganyang Piyungan - fatmawati, ery; Endah Tri Wahyuni; Dyah Muliawati (ABDIMAS Madani, 2025)
High-risk pregnancy is a condition in which the pregnancy carries a higher potential for complications, both for the mother and the fetus, thus requiring intensive monitoring. Health education plays a vital role in increasing pregnant women's knowledge and awareness of danger signs during pregnancy, risk factors, and the importance of routine antenatal check-ups. The aim of this community service activity is to improve the understanding of pregnant women, families, communities, and health cadres in recognizing pregnancy risks at an early stage. The methods used include interactive counseling and group discussions. The results of the activity showed an increase in participants' knowledge and positive attitudes towards the importance of early detection and care for high-risk pregnancies. Through appropriate health education approaches, it is expected that pregnant women will be better prepared and more alert throughout their pregnancy, as well as capable of making informed decisions regarding their health.